LABOR PHYSICAL EXERCISES AND ITS EFFECT IN THE HEALTH OF THE WORKER (Fiep Bulletin - online, 2013)
The objective of this study is to ahead evaluate the behavior of servers of the monotonous and repetitive work that involves servers of three sectors of the University HUB/hospital of Brasilia, by means of the QVT politics. The sample of this study was constituted by three sectors of the HUB: 16 servers of the CME/Centro de Materiais and Esterilização; 05 servers of the CTI/Centro of Intensive therapy and 05 servers of the Surgical Pediatrics, totalizing 29 servers.
Keywords: exercise repetitive work; QVT